Pengaruh Kecerdasan Spiritual dan Motivasi Individu terhadap Kinerja Ramah Lingkungan - Sahmin Madina (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2022)
The objective research was to determine the effect of spiritual intelligence and motivation of individuals in a performance-friendly environment. This research was conducted from June until August 2021—the entire study population of students at IAIN Sultan Amai Gorontalo. The sample was selected using the probability sampling technique. Research sample, as many as 111 students use the formula, Slovin because the number can represent the existing population. This study uses a survey method using google forms. The approach study uses a quantitative approach. Research results show positive and significant partial and simultaneous spiritual intelligence and motivation for individuals to perform in a friendly environment. Variable free to have the most decisive influence, and the most significant contribution to variable bound is spiritual intelligence. Based on research findings, it is concluded that if you want to improve a performance-friendly environment, factors such as spiritual intelligence and motivation need to be improved.